Comparison of 311‐nm Titanium:Sapphire laser and 308‐nm excimer laser treatment for vitiligo: A randomized controlled non‐inferiority trial. Issue 3 (25th January 2019) - Bae, Jung Min; Eun, Sung Hye; Lee, Han Na; Kim, Gyong Moon; Grimes, Pearl E.; Lee, Ji Hae
Abstract : Objectives: The 308‐nm excimer laser (EL) has been widely used for localized vitiligo. The recently developed Titanium:Sapphire laser, emits a wavelength of 311 nm, would be expected to be as effective as excimer laser in treatment of vitiligo but few controlled trials have been reported. We sought to compare the efficacy and safety of the TSL and EL as vitiligo treatments. Methods: A randomized controlled non‐inferiority trial based on split‐body was conducted. Patients with stable vitiligo between June 2016 and May 2017 were enrolled. Paired symmetrical vitiligo lesions were randomized to either the EL or TSL treatment group, and treated with a 308‐nm EL or a 311‐nm TSL twice weekly for 12 weeks. The extent of repigmentation was assessed every 4 weeks, and the non‐inferiority margin was set to 10%. We also recorded any adverse events. Results: Seventy‐four paired lesions in 21 patients were assigned to both the EL group or TSL group. The mean difference between two groups (EL minus TSL) was −2.862%, and the 95% confidence interval (−6.531% to 0.807%) was lower than the non‐inferiority margin. No serious adverse events were noted in either group. Conclusions: The Titanium:Sapphire laser showed similar therapeutic effect to excimer laser in localized vitiligo with good safety profiles in this non‐inferiority randomized controlled trial. The Titanium: Sapphire laser can serve as an alternative treatment option for localized vitiligo. Lasers Surg. Med. 51:239–244, 2019. © 2019 Wiley Periodicals, Inc.